THE USE OF DRILLING TECHNIQUE IN LEARNING STRESS PATTERN OF ENGLISH WORDS - Kristiana, Vera; Mahraini, Rani (PHILOLOGY Journal of English Language and Literature, 2024)
Drilling means listening to a model, provided by the teacher, or a tape or another student, and repeating what is heard. This is a repetition drill, a technique that is still used by many teachers when introducing new language items to their students. The teacher says (models) the word or phrase and the students repeat it. Drilling provides learners with intensive practice in hearing and saying particular words or phrases. They can help learners get their tongues around difficult sounds or help them imitate intonation that may be rather different from that of their first language. It is a right choice to learn stress pattern of English words because students can memorize those patterns easily and quickly. Intonation patterns that are crucial to meaning may also be usefully practised through drilling.